Experiences of siblings to children with autism spectrum disorder - Mokoena, Naledi; Kern, Anwynne (Frontiers in Psychiatry, 2022)
Autism Spectrum Disorder (ASD) is prevalent globally resulting in increased awareness and understanding of the disorder internationally and to a lesser extent in Southern African countries. This understanding has predominantly been in relation to the impact of the disorder on the neurodivergent child and family relations. Internationally limited research has explored the impact on neurotypical siblings who have been raised alongside children diagnosed with ASD, with a dearth of such studies emerging from the South African context. The importance of neurotypical siblings’ developmental experiences emerging from their immediate environment is significant within the traditionally collectivist nation of South Africa. For this reason, this study aimed to explore South African neurotypical siblings’ experiences of living with a brother or sister diagnosed with ASD; through a qualitative study adopting an Interpretative Phenomenological design. Semi-structured interviews, aimed at generating demographic data and exploring the experiences of being raised alongside a sibling diagnosed with ASD, were conducted with eight university students. The data generated were analyzed employing the five stages of the Interpretive Phenomenological Analysis approach. Themes of Emotional Burden, Perceived Family Dynamics, Acceptance, and Identity Development emerged through data analysis. Participants reported experiences of pre-mature development, unfair treatment, and feelings of being overburdened, along with reported efforts towards acceptance of their sibling’s diagnosis, and support from community members. Consequently, an understanding that their neurodivergent sibling played a key role in the development of their identities and career trajectories emerged. The impact of being raised alongside a sibling diagnosed with ASD highlights the need for additional support for neurotypical individuals, supported by programs to enhance awareness about ASD in the general South African community. These interventions would be aimed at mitigating the impact of heightened childhood stress, stigmatization, and marginalization.